Odpowiedź:
Zadanie 2:
2b = p(3-x)
[tex]\frac{2b}{p} = 3-x[/tex]
[tex]\frac{2b}{p} - 3 = -x[/tex]
[tex]-1(\frac{2b}{p} - 3)=-1(-x)\\-\frac{2b}{p} + 3=x\\[/tex]
założenie:
[tex]p\neq 0[/tex]
Zadanie 3:
[tex]3a = \frac{2b -2}{2k}[/tex]
[tex]3a =\frac{ 2(b-1)}{2k} \\3a = \frac{ (b-1)}{k}\\k = \frac{ (b-1)}{3a}[/tex]
założenie:
[tex]k\neq 0\\a \neq 0[/tex]
Zadanie 4:
[tex]F + 2 = H - 10k(E + 2)\\F + 2 - H = -10k(E + 2)\\\frac{F + 2 - H}{(E + 2)} = -10k\\\\ \frac{\frac{F + 2 - H}{(E + 2)}}{10} = -k\\\frac{F + 2 - H}{(E + 2)}* \frac{1}{10} = -k\\\\\frac{F + 2 - H}{10(E + 2)} = -k\\\\-1(\frac{F + 2 - H}{10(E + 2)} ) =-1( -k)\\-\frac{F + 2 - H}{10(E + 2)} =k\\[/tex]
założenie:
[tex]E \neq -2[/tex]
Szczegółowe wyjaśnienie: